TOWARDS A SUSTAINABLE POST-WAR RECOVERY: THE ROLE OF UNIVERSITIES IN UKRAINE'S ECONOMIC, ENVIRONMENTAL, AND SOCIAL TRANSFORMATION - Nataliia Kholiavko (Baltic Journal of Economic Studies)
The purpose of the present paper is to investigate the role and contribution of universities and students in supporting post-war recovery based on the principles of sustainable development. Methodology. The research employed a survey method, with students from Ukrainian higher education institutions selected as the primary target group of respondents. A total of 151 students from a variety of academic disciplines participated in the survey, which was conducted electronically via Google Forms. The questionnaire comprised 35 questions with the aim of assessing young people's understanding of the fundamental principles of the Sustainable Development Goals, as well as the roles of universities and students in achieving them. The questionnaire comprised a number of question types, including diagnostic, evaluative, behavioural and motivational questions. The content of the questionnaire encompassed a range of topics, including general principles of sustainable development, economic aspects (innovation, infrastructure, labour, use of natural resources), environmental aspects (ecosystems, water resources, biodiversity, etc.), and social aspects (inequality, gender balance, inclusion). In addition, the questionnaire posed questions related to partnerships and the impact of universities on achieving the SDGs. The methodological framework of the study is based on the Sustainable Development Concept. The article provides substantiating evidence for the hypothesis that this concept can be applied in Ukraine's post-war recovery process. In view of the fact that sustainable development encompasses economic, social, and environmental components, the questionnaire was structured accordingly to reflect each of these dimensions. Results. The article presents the results of an analysis of respondents' answers to questions related to the economic component of sustainable development. The study revealed a reasonably accurate understanding among young people of the internal essence of the Sustainable Development Goals. The majority of respondents demonstrated an adequate understanding of the significance of sustainable development in ensuring national economic growth. While acknowledging the pivotal function of academic institutions in fostering sustainable development, students exhibit a moderate degree of self-awareness concerning their individual contributions to the achievement of the SDGs. Findings. The author suggests that Ukraine’s model of sustainable post-war recovery should be based on the four "R" pillars, including the economy and the higher education system: Relationships, Renovation, Resilience and Revampment. In light of the rapid advancement of digital technologies, the article also suggests integrating digital solutions into the implementation of the Sustainable Development Goals (SDGs) and strengthening security measures in Ukraine during the post-war period.